Gambaran Penggunaan Complementary Alternative Medicine (Cam) Pada Pasien Hipertensi Di Wilayah Kerja Puskesmas Tegallalangi - Devi, Luh Pradnya Paramita Devi; Septiari, I Gusti Ayu Agung; Mayun, I Gusti Ngurah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Hypertension is circumstances Where pressure blood systolic more of 140mmHg and pressure blood diastolic more than 90 mm Hg. Complementary Alternative Medicine (CAM) is no- conventional treatment addressed For increase degrees health public through education structured with strength , safety And effectiveness based knowledge knowledge biomedical . CAM covers use herbs , vitamins and minerals, Meditation , yoga, acupuncture And therapy massage . Objective study This is For know description use cam patient hypertension in Public health center Tegallalang I. Method study This is descriptive non - experimental with method Cross Sectionals. Sample totaling 120 people . Results study This form analysis prevalence And characteristics CAM use on patient hypertension in region Work Public health center Tegallalang I. Use of CAM by patient hypertension as much as 70% part big respondent use CAM not since diagnosis (82.9%) at most respondent use accompanying CAM treatment treatment conventional (74.7%) dominant recommended by family (60.0%) with most reasons accessibility (availability) (65.7%). Analysis pattern the most use of CAM used respondent were herbs (32.9%), the most abundant herbs used is celery (47.8%) with form most preparations _ that is digestion (43.5%) and method the most processing that is with method boiled especially first (87.0%) with dose use the most One glass in a day (70%). Conclusion in study This patient hypertension in region Work Public health center Tegallalang I, especially in Village Tegallalang And Village Keliki , patient hypertension based on characteristics sociodemography dominant female (73.3%), aged 41-50 years (52.5%) education finally high school (45.0%), 70 people (58.3%) use CAM, dominant used No since diagnosed hypertension (82.9%), type of CAM used that is herbal biologics (32.9%).